The relationship between fracture toughness and tensile property in high-strength steels. (January 2022) - Li, H.F.; Wei, J.L.; Yang, S.P.; Liu, Y.Q.
Highlights: The quantitative relationship between fracture toughness and tensile property in high-strength steels. The similar fracture mechanism would be elaborated in the tensile and K IC specimen. The fracture mechanism is mainly attributed to the various microstructures: grain size, dislocation density and precipitated carbides. It provides a new insight for the estimation of fracture toughness. Abstract: In the present work, the fracture toughness and tensile property of 40CrNiMoA high-strength steel were systematically investigated. The experimental results reveal that the ultimate tensile strength of 40CrNiMoA steel decreases gradually with improving the tempering temperature, while the fracture toughness reveals a reverse trend to the tensile strength. The fractography shows the consistency of quasi-static fracture characteristic in the tensile and K IC specimens. The complicated fracture mechanism of 40CrNiMoA steel is mainly attributed to the various microstructures: grain size, dislocation density and precipitated carbides. Additionally, based on the macro/micro- fracture mechanisms and energy principle, we proposed the relation between fracture toughness and macroscopic tensile parameters. The new model would provide an effective strategy to predict the fracture toughness of high-strength steels, which can be further applied to other engineering materials such as aluminum and titanium alloys.